Atomic hydrogen deficiency in spiral galaxies in clusters - Shaldenkova, E.S. (Advances in Astronomy and Space Physics, 2011)
We consider the new method for atomic hydrogen deficiency estimations. The main idea is to use the empirical relation between total HI mass and specific angular momentum of the disk for isolated galaxies. The method was compared with the standard one, based on dependence of HI mass on optical diameter and galaxy type. They both were applied to Virgo and Coma cluster galaxies and to Local Volume galaxies. Also we investigated possible mechanisms responsible for HI deficiency in cluster spirals.